Concomitant conus medullaris arteriovenous shunts and sacral dural arteriovenous fistulas: pathophysiological links related to the venous drainage of the lesions in a series of five cases. (19th January 2018) - Rosi, Andrea; Consoli, Arturo; Condette-Auliac, Stéphanie; Coskun, Oguzhan; Di Maria, Federico; Rodesch, Georges
Abstract : Background: Spinal cord arteriovenous shunts (scAVSs) are a group of lesions located in the spinal cord itself or in the surrounding structures. The most common scAVSs are spinal dural arteriovenous fistulas (sDAVFs), which are acquired lesions. The pathogenesis of sDAVFs involves thrombosis and venous hypertension as trigger factors. Intradural scAVSs such as spinal cord arteriovenous nidus type malformations (AVMs) and pial arteriovenous fistulas are less common than sDAVFs and are considered to have a so-called 'congenital' origin. The association between different concomitant scAVSs is very rare and the association of sDAVFs with intradural scAVSs has been described in only a few case reports. Methods: We describe a case series of five patients presenting with a conus medullaris AVS associated with a lower lumbar or sacral DAVF. Results: Three of our patients were <30 years old at presentation. In four of these five cases the intradural scAVS drained caudally, engorging the epidural plexus in the same location as the sDAVF. In only one case, who presented with thrombosis of the drainage of the main compartment of a conus medullaris pial AVF, was the location of the DAVF opposite to the location of the residual drainage. Conclusion: We discuss the pathophysiological link between scAVS and sDAVF on the basis of the rarity of the DAVF, the uncommon association between scAVS and sDAVF, the presence of sDAVF in young patients, and the venous hypertension created by the venous drainage towards the sacral area responsible for angiogenesis creating the dural shunt.